Hand-assisted right laparoscopic nephrectomy in living donor - Meyer,Fernando (2005)
OBJECTIVE: To assess results obtained with the authors' technique of right hand-assisted laparoscopic nephrectomy in living kidney donors. MATERIALS AND METHODS: We retrospectively analyzed 16 kidney donors who underwent hand-assisted right laparoscopic nephrectomy from February 2001 to July 2004. Among these patients, 7 were male and 9 were female, with mean age ranging between 22 and 58 years (mean 35.75). RESULTS: Surgical time ranged from 55 to 210 minutes (mean 127.81 min) and warm ischemia time from 2 to 6 minutes (mean 3.78 min) with mean intra-operative blood loss estimated at 90.62 mL. There was no need for conversion in any case. Discharge from hospital occurred between the 3rd and 6th days (mean 3.81). On the graft assessment, immediate diuresis was seen in 15 cases (93.75%) and serum creatinine on the 7th post-operative day was 1.60 mg/dL on average. Renal vein thrombosis occurred in 1 patient (6.25%) who required graft removal, and lymphocele was seen in 1 recipient (6.25%). CONCLUSION: Hand-assisted right laparoscopic nephrectomy in living donors is a safe and effective alternative to open nephrectomy. Despite a greater technical difficulty, the procedure presented low postoperative morbidity providing good morphological and functional quality of the graft on the recipient.